A narrative review of strategies of human fertility and sustainable development - Saad, Alia Osman Sayed (Edelweiss Applied Science and Technology, 2025)
The study aims to examine five aspects, including the environmental impact, quality of life, contraceptive use, fertility awareness programs, and control of non-communicable diseases as sustainable development objectives to improve reproductive health and sexual well-being of men and women in the Middle East. The United Nations (UN) established eight Millennium Development Goals (MDGs) in 2000, with the target year of 2015 in consideration. Among their goals were the elimination of extreme poverty and hunger, the provision of access to primary education for all, the advancement of women and the promotion of gender equality, and the reduction of infant and maternal mortality. The study used international guidelines or measurement tools to summarize sustainable development goals to ensure improved human fertility and reproductive health, particularly in the Middle East. This study uses a narrative review methodology. The study highlighted the importance of environmental, economic, and healthcare goals to improve reproductive health outcomes in the Middle Eastern population and the requirement for the development of homogeneous procedures for initiating any fertility awareness campaign or instrument before hands-on application. This study provided a baseline framework for developing and implementing sustainable reproductive goals related to human reproductive health and fertility in the Middle East region.